Elderly patients with myocardial infarction selected for conservative or invasive treatment strategy - Libungan B (Dove Medical Press, 2015)
Berglind Libungan,1 Thomas Karlsson,2 Per Albertsson,1 Johan Herlitz3 1Department of Cardiology, Sahlgrenska University Hospital, Gothenburg, Sweden; 2Center for Applied Biostatistics, Occupational and Environmental Medicine, Sahlgrenska Academy at University of Gothenburg, Gothenburg, Sweden; 3Sahlgrenska University Hospital and Center for Prehospital Research, Western Sweden University of Borås, Borås, Sweden Background: There are limited data on patients aged >75 years with myocardial infarction (MI), especially those who are treated conservatively.Hypothesis: There are important differences in the clinical characteristics and outcome between elderly MI patients selected for invasive or conservative treatment strategy.Methods: A total of 1,413 elderly patients (>75 years old) admitted to Sahlgrenska University Hospital, Gothenburg, Sweden with a final diagnosis of acute MI in 2001 or 2007, were divided into two groups, those who underwent a conservative treatment strategy (conservative group [CG], n=1,169) and those who underwent coronary angiography and were revascularized if indicated (invasive group [IG], n=244).Results: Other than higher age in the CG, there were no significant differences in traditional risk factors such as hypertension, diabetes, and smoking in the two groups. A higher proportion of patients in the CG had a history of heart failure and cerebrovascular disease. The hazard ratio (with 95% confidence interval), adjusted for potential confounders, for 5 year mortality in the IG in relation to the CG was 0.49 (0.39, 0.62), P<0.0001. Overall, in the elderly with MI, the proportion who underwent an invasive treatment strategy doubled from 12% in 2001 to 24% in 2007, despite a slightly higher mean age.Conclusion: Elderly patients with MI in the CG (no coronary angiography), were generally older and a higher proportion had chronic diseases such as congestive heart failure and cerebrovascular disease than those in the IG. Our data suggest that the invasive treatment strategy is associated with better outcome. However, randomized trials will be needed to determine whether revascularization procedures are beneficial in elderly patients with MI, in terms of less symptoms, better outcome, and improved quality of life. Keywords: elderly, myocardial infarction, acute coronary syndrome, aged